E-Shop Berbasis OpenCart untuk Meningkatkan Penjualan Tanaman Pada UMKM Rumah Bunga - Arfandi, Adnan; Annas, Firdaus; Imam Dwi Maulana, Muhammad (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The Flower House Micro, Small and Medium Enterprises in Mandau District face challenges in increasing sales of ornamental plants because they still use limited conventional marketing methods to reach customers. This condition hampers business growth and competitiveness of Micro, Small and Medium Enterprises amidst the increasing need for digitalization. This article aims to design and develop an OpenCart-based e-shop which can be an effective solution for expanding market reach and increasing sales. This research uses research and development (R&D) methodology with the ADDIE development model The results of this research are in the form of web-based promotional media using the Opencart application which is designed to meet the needs of Micro, Small and Medium Enterprises in managing and marketing products digitally. The findings of this research indicate that OpenCart acts as an effective supporting media in increasing the competitiveness of ornamental plant products in Mandau District. This application not only functions as an e-commerce platform for buying and selling transactions, but is also a strategic tool that helps Micro, Small and Medium Enterprises promote their products more widely and efficiently. With superior features such as an informative product catalogue, integrated stock management, secure payment system, and shipping support, OpenCart provides a complete digital solution for Micro, Small and Medium Enterprises. The implications of this research show that an OpenCart-based e-commerce platform can be an effective digital solution to help Micro, Small and Medium Enterprises face marketing challenges in the modern era. It is hoped that this e-shop can become a digitalization model that can be used by other Micro, Small and Medium Enterprises to increase the competitiveness and sustainability of their business.